The role of Bio and organic fertilization in the preparation and content of some nutrients for Pomelo seedlings Citrus grandis L. grafted on different rootstocks - A. AL- Abbasi, Ghaleb B.; A. AL-Zuhairi, Faris F. (Journal of Kerbala for Agricultural Sciences, 2017)
The study was carried out at citrus production garden of the Ministry of Agriculture- General directorate of Horticulture and Forestry in the province of Karbala holy, Alhundia town between 1/03/ 2016 and 1/12/2016 on 6 months Pomelo seedlings grafted on two rootstocks of citrus including Fulcamaryana and Bitter orange to study the effect of rootstocks, organic fertilizer (Rice straw residues) and bio-fertilization by different species of bacteria including Azospirillum brasilense , Azotobacter chroococcus , Bacillus subtilis and their interactions on preparation and content of nutrients. The experiment was carried out using Randomized Complete Block Design (RCBD) with two factors. This study included 32 treatments with 3 replicates for each treatment and each replicated with three seedlings where mean comparisons were performed using LSD test at 5% level of significance. The results showed that treatment of Azospirillium, Azotobacter and Bacillius with organic fertilization was superior in leaves content of nitrogen, leaves content of phosphorus and phosphorus quantity in the soil which were 2.450%, 0.579% , 17.63 mg/kg respectively compared to control treatment which gave the lowest values. Although the treatment of Azospirillium, and Bacillius with organic fertilization was superior in leaves content of potassium (1.54%), Azopirillum, Azotobacter with organic fertilization treatment was superior in soil content of nitrogen (11.08 mg/kg). In case of rootstocks, results showed that pomelo seedlings grafted on Fulcamaryana had a highest level of leaves content of phosphorus and potassium (0.492% and 1.34% respectively). While, pomelo seedlings grafted on Bitter orange was superior in phosphorus quantity in the soil 11.06 mg/kg-1. There was no significant differences between different rootstocks in both leaves content of total nitrogen and nitrogen quantity in the soil.